Himpunan undang-undang/peraturan pemerintah keputusan/instruksi Presiden RI dan peraturan/keputusan/instruksi menteri dalam negeri tahun 1982 - INDONESIA. Undang-undang, Peraturan dsb (1982)
...jil ilus 21 cm